2005
DOI: 10.1364/opex.13.002289
|View full text |Cite
|
Sign up to set email alerts
|

Soliton collapse and bunched noise-like pulse generation in a passively mode-locked fiber ring laser

Abstract: A passively mode-locked soliton fiber ring laser with dispersion managed cavity is reported. The laser emits intense bunched noise-like pulses including the transform limited pulses. The optical spectrum of the laser emission has a bandwidth as broad as 32.10 nm. It was found that purely depending on the linear cavity phase delay the laser could be switched between the soliton operation and the noise-like pulse emission. Numerical simulations showed that the laser emission was caused by the combined effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
98
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 211 publications
(105 citation statements)
references
References 0 publications
7
98
0
Order By: Relevance
“…[16,17,18,19,20,21,22,23]) we found that only the three systems considered in this paper exhibited NLPs in our simulations. 2 It would also be desirable to make more careful calculations of the bifurcations, including precise continuation to bifurcation points, and calculation of the spectra.…”
Section: Discussionmentioning
confidence: 53%
“…[16,17,18,19,20,21,22,23]) we found that only the three systems considered in this paper exhibited NLPs in our simulations. 2 It would also be desirable to make more careful calculations of the bifurcations, including precise continuation to bifurcation points, and calculation of the spectra.…”
Section: Discussionmentioning
confidence: 53%
“…The stretched pulse operation, together with increased cavity length [60,72], helps in realization of pulse energies much higher than conventional soliton based mode locked lasers. However, higher pulse energies bring about additional nonlinear interactions, resulting in dispersive wave generation [73,74], pulse break up and formation of noisy pulses [75], and even generation of rogue waves [76][77][78][79]. The intrinsic variability of the mode locked regimes gives rise to further diversity of outputs [80].…”
Section: Spatio-temporal Dynamics Of Partially Mode Locked Fibre Lasersmentioning
confidence: 99%
“…The pattern of multipulse inside the cavity, however, is stochastically distributed, e.g. bound solitons [9], bunched soliton [10] [11], and harmonic mode-locking with equal spacing [12] [13]. As far as controllability is concerned, it is very interesting to actively manipulate the distribution of multipulse inside the fiber cavity.…”
Section: Introductionmentioning
confidence: 99%